The analysis of conflicts concerning urban area use: A case of Olsztyn (Poland) - Zróbek, Sabina; Zachaś, Magdalena (International Journal of Strategic Property Management, 2010)
The aim of this study was to analyze the conflicts that arise in Poland at the stage of working out (elaborating) local spatial management plans, issuing development orders concerning land development conditions and building permits, and the conflicts that are reported by the inhabitants to the municipal police. The analysis of the conflicts was conducted on the example of the city of Olsztyn. The research focuses on the quantitative and qualitative aspects of the conflicts, and examines the causes for their existence. The goal of the study was to emphasize the importance of conflict identification while making the decisions referring to land use.First Published online: 18 Oct 2010